Litigation risk and IPO underpricing: evidence from federal judge ideology - Chen, Yangyang; Goyal, Abhinav; Veeraraghavan, Madhu; Zolotoy, Leon (Review of Accounting Studies, 2026)
Using federal judge ideology as an exogenous measure of issuing firms’ litigation risk, we document that the initial public offerings (IPOs) of the firms headquartered in more liberal circuits are more underpriced. The effect is mitigated when plaintiffs’ pleading standards are more stringent and is amplified when judges have more discretion in their decisions. The effect is also amplified among deep pocketed issuing firms, while it is mitigated among issuing firms hiring reputable intermediaries in the IPO process. The results of additional analysis suggest that issuing firms located in more liberal circuits are more likely to become targets of lawsuits after their IPOs and that these lawsuits are less likely to be dismissed by the courts and result in larger settlements. Collectively, our findings underscore the salience of litigation risk stemming from the issuing firms’ legal environment in driving IPO underpricing.